UWB microstrip patch antenna with 5G lower band notch characteristics - Mahfuz, M M Hasan; Islam, Md Rafiqul; Habaebi, Mohamed Hadi; Abdul Malek, Norun; Sakib, Nazmus; Hossain, A K M Zakir (International Association of Online Engineering, 2022)
For fifth generation (5G) lower band wireless application at a frequency of (4.5–5.5) GHz, recently ASEAN region countries have suggested 5G forums and band rejection antennas for 5G (4.5–5.5) GHz lower band. A UWB antenna has been constructed and suggested by use of the Roger RT5880 with defected ground on a rectangular radiating patch and a ring shape type of resonator (RSR) on ground plane to achieve the desired performance. It was decided to construct a band rejection within UWB antenna for 5G which included adding a rectangular slot on the radiating patch as well as placing RSR to the ground plane of the proposed antenna. The results support the theory that the antenna is capable of transmitting and receiving in the UWB except band notched bandwidth. Additionally, the results show that the antenna possesses good performance across the whole UWB spectrum with a gain of 4.6 dBi. This, in addition to its ability to support the lower 5G band notched, is why the suggested antenna is a good contender for future 5G wireless implementations within UWB bandwidth.